2021
DOI: 10.1007/s12250-021-00383-x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Evolution of H7N9 Subtype Influenza Virus under Vaccination Pressure

Abstract: No avian H7N9 outbreaks have occurred since the introduction of H7N9 inactivated vaccine in the fall of 2017. However, H7N9 is still prevalent in poultry. To surveil the prevalence, genetic characteristics, and antigenic changes of H7N9, over 7000 oropharyngeal and cloaca swab specimens were collected from live poultry markets and farms in 15 provinces of China from 2017 to 2019. A total of 85 influenza virus subtype H7N9 strains were isolated and 20 representative strains were selected for genetic analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
(31 reference statements)
0
23
0
Order By: Relevance
“…Only a small proportion of cases were detected in domestic ducks, pigeons, quails, and other wild birds in the first five epidemic waves [46][47][48][49]. Recent studies showed that the HP H7N9 virus was still detected in ducks and peacocks after wave 5 [16,17]. We found HP H7N9 AIVs primarily in chicken, especially from layers and partially from broilers, indicating that the HP H7N9 mainly infects the longer-lived layers or breeders in the farming industry.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Only a small proportion of cases were detected in domestic ducks, pigeons, quails, and other wild birds in the first five epidemic waves [46][47][48][49]. Recent studies showed that the HP H7N9 virus was still detected in ducks and peacocks after wave 5 [16,17]. We found HP H7N9 AIVs primarily in chicken, especially from layers and partially from broilers, indicating that the HP H7N9 mainly infects the longer-lived layers or breeders in the farming industry.…”
Section: Discussionmentioning
confidence: 69%
“…Besides, sites 125/130 mutations induced a 5-fold difference in the neutralizing activity against the field virus [60]. Of note, the antigenicity of HP H7N9 AIV in recent years has drifted rapidly and significantly under intensive vaccination [10,12,[16][17][18]. Therefore, the antigenicity of the circulating HP H7N9 virus needs to be closely monitored, and the antigenic composition of vaccines needs to be updated as needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, after the emergence of the highly pathogenic H7N9 avian influenza virus during the fifth wave, the H7N9 virus caused a sharp rise in human infection, resulting in 1,568 laboratory-confirmed cases and 616 deaths as of July 7, 2021 (http://www.fao.org/ag/againfo/programmes/en/empres/H7N9/ situation_update.html). More importantly, some novel biological features of the H7N9 virus, such as immune escape mutations and antigenic drift were discovered in H7N9 variants (2)(3)(4). Thus, there is still a possibility of an H7N9 pandemic outbreak.…”
Section: Introductionmentioning
confidence: 99%